Paula Deen's southern cooking bible : the classic guide to delicious dishes with more than 300 recipes - Deen, Paula H., 1947-; Clark, Melissa (New York : Simon & Schuster, 2011)
A full-length recipe collection by the Food Network star and author features comprehensive coverage for more than three hundred Southern-inspired recipes and related cooking techniques.
Includes index.
Keywords: Cooking, American -- Southern style; Southern cooking; American cooking; Cookbooks